Potential of medicinal plants to inhibit neurodegenerative activities in diabetes: a systematic review - Phaik Har Yong; Wong Xue Yi1; Meram Azzani; Rhanye Mac Guad; Zhi Xiang Ng (Journal of Young Pharmacists, 2024)
Several studies have established that diabetes can exacerbate the neurodegeneration process. Some studies have reported the potential use of medicinal plants to inhibit neurodegenerative activities in diabetes. Therefore, this systematic review aims to evaluate the potential of medicinal plants to ameliorate neurodegenerative activities in diabetes. This systematic review was reported according to PRISMA guidelines. A systematic search was performed in four databases which were PubMed, Scopus, Google Scholar and Science Direct. Seven articles that fulfilled the inclusion criteria were selected for reporting this review. The medicinal plants reported in these articles were studied for their blood glucose lowering effect, acetylcholinesterase inhibitory activity and cognitive improvement ability through a behavioural test known as the Morris water maze. The medicinal plants such as Liuwei Dihuang Decoction (LWDHD), Flos Puerariae Extract (FPE), methanolic leaf extract of Peristrophe bicalyculata (MEPb), Ethanol Extract of Clitorea ternatea (EECT), Lychee Seed Extract (LSE) Andrographis paniculata extract (AP), andrographolide and Petroleum Ether Extract of Carica papaya Seeds (PEECPS) have shown significant result in Morris water maze test and acetylcholinesterase inhibitory activity, suggesting their ability to improve cognitive behaviour. They were also reported to have blood glucose lowering effect except for MEPb. LWDHD, FPE, MEPb, EECT, LSE, AP, andrographolide and PEECPS reported in these articles have shown potential in improving cognitive behaviour of diabetic animals. They were also reported to have anti-diabetic effects except for MEPb. However, more studies and research should be conducted to ensure the potential and safe use of these medicinal plants.